Time estimation and passage of time judgment predict eating behaviors during COVID-19 lockdown - Isham, Eve A.; Lomayesva, Sara; Teng, Jiaxuan (Frontiers in Psychology, 2022)
Poor eating habits often lead to health concerns. While mental health conditions such as stress and anxiety have been linked as predictors for eating behaviors, cognitive factors may also contribute to eating practices during the early stages of the mandatory COVID-19 lockdown. In the current study, participants responded to a survey that asked them to judge the passing of time (PoTJ) and to produce short intervals (via a time production task) as an index of the internal clock speed. Additionally, they responded to questions about snacking frequency and the tendency to overeat during lockdown. We observed that those who judged time to pass slowly also reported a greater tendency to snack and overeat during the pandemic. Additional analysis also revealed that the effect of PoTJ on snacking is moderated by the internal clock speed such that those who felt time was passing by slowly, and in combination with a faster internal clock (as indexed by shorter duration production), had a greater tendency to snack. The results suggest that different aspects of temporal cognition play potential roles in influencing different types of eating behaviors. Our findings therefore have implications for eating disorders, along with the potential of time-based intervention or behavioral modification approaches.